2020
DOI: 10.1101/2020.10.11.334888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Native structure of flagellar MS ring is formed by 34 subunits with 23-fold and 11-fold subsymmetries

Abstract: The bacterial flagellar MS ring is a transmembrane complex acting as the core of the flagellar motor. It not only acts as the template for rod and C ring assembly but also houses the type III protein export gate for assembly of the rod, hook and filament. The cytoplasmic C ring, involved in torque generation and rotation switch, is directly attached to the MS ring, and a symmetry mismatch between 26-fold MS ring and 34-fold C ring had been a long puzzle as to whether this would play some role in motor function… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…The crystal structure of RBM1 and RBM2 together with the cryoEM structure of the MS-ring, including a high-resolution structure of the S-ring (RBM3), revealed the periplasmic part of the MS-ring structure. Our cryoEM analysis of the MS-FliG ring complex demonstrated that the MS-ring in the basal body is made up of 34 FliF subunits and is consistent with results of the recent cryoEM studies of the MS-ring formed by fulllength FliF and the MS-ring in the flagellar basal body (25). The S-ring with a cylindrical collar is shaped like a boater hat with C34 symmetry, whereas the inner part of the Mring has a gear wheel-like structure consisting of the core C23 symmetry inner ring and the C11 symmetry cogs surrounding it.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The crystal structure of RBM1 and RBM2 together with the cryoEM structure of the MS-ring, including a high-resolution structure of the S-ring (RBM3), revealed the periplasmic part of the MS-ring structure. Our cryoEM analysis of the MS-FliG ring complex demonstrated that the MS-ring in the basal body is made up of 34 FliF subunits and is consistent with results of the recent cryoEM studies of the MS-ring formed by fulllength FliF and the MS-ring in the flagellar basal body (25). The S-ring with a cylindrical collar is shaped like a boater hat with C34 symmetry, whereas the inner part of the Mring has a gear wheel-like structure consisting of the core C23 symmetry inner ring and the C11 symmetry cogs surrounding it.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, 21 or 22 copies of RBM2 form a ring in the inner part of the M-ring, and this is surrounded by 9 or 10 globular densities composed of RBM1 and RBM2. However, a few copies of RBM2 and more than 20 copies of RBM1 are missing in these structures, and the variation in the subunit stoichiometry is likely to be an artifact due to C-terminal truncations of FliF because the MS-ring in the flagellar basal body, as well as that formed by full-length recombinant FliF, showed only 34-fold rotational symmetry ( 25 ). Moreover, the cryoEM analysis of the purified the flagellar basal body showed a C23 symmetry at the inner part of the M-ring ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent structural analysis of the MS ring revealed its symmetry to be 33-fold with a variation from 32 to 35 (Ref. 27 ), and the analysis of the flagellar basal body showed the MS ring to have 34-fold symmetry without variation and the C ring to have a small symmetry variation around 34-fold 28 . These results indicate the number of FliG on the C ring is mostly 34 and therefore invalidate the previous interpretation that the 26 steps per revolution reflect the elementary process of torque generation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the LP ring is a stable component of the hook-basal body even after its isolation from the cell, the LP ring easily slips off the rod when the basal body is isolated without the hook 6,7,28 , indicating very weak interactions between the rod and LP ring to keep the LP ring in the proper position around the rod. In the absence of FlgH, however, the basal body formation stops just after completion of P ring assembly by FlgI around the rod to form a structure called “candlestick” 7,29 , indicating that the P ring is tightly attached to the rod until the L ring is assembled above it.…”
Section: Discussionmentioning
confidence: 99%
“…The MS ring is constructed by assembling dozen copies of FliF, a protein with two transmembrane segments (10)(11)(12). The subatomic structure of the MS ring was determined by cryo-electron microscopy, although the N-terminal and C-terminal regions were not found in S. enterica (13,14). The C ring is composed of three proteins, FliG, FliM, and FliN, and forms a complex with the MS ring via FliG (15).…”
mentioning
confidence: 99%